The Indonesian Version of the Online Learning Motivated Attention and Regulatory Strategies (OL-MARS v.2) Scale - Gani, Suriati Abdul; Murwani, F. Danardana; Hitipeuw, Imanuel; Radjah, Carolina L. (Faculty of Psychology, Universitas Gadjah Mada, 2024)
The increasing use of ICT and the tendency for media multitasking among students have raised concerns about their negative impact on attention and the challenges they pose to regulation strategies. This study aimed to adapt and validate the Indonesian version of the Online Learning Motivated Attention and Regulatory Strategies (OL-MARS v.2) scale among undergraduate university students. The OL-MARS v.2 is a 24-item scale measuring two main constructs: perceived attention problems (PAP) and self-regulatory strategies (SRS). PAP includes three subscales: perceived attention discontinuity (PAD), lingering thoughts (LT), and social media notifications (SMN), while SRS comprises behavioral strategies (BS) and outcome appraisal (OA). The scale was administered to 1,360 undergraduate students at a private university in Indonesia. Alpha coefficients for the total scores ranged from 0.463 to 0.800, indicating overall good to acceptable reliability, although the LT subscale showed the lowest alpha (0.463), which was acceptable but not ideal. Confirmatory factor analysis (CFA) was performed to evaluate the model fit. The OL-MARS v.2 shows potential as a valuable tool for assessing students' attention states and self-regulation strategies in online learning environments.